Effects of globa l warming on insect natural enemies - BAI Yueliang; ZHOU Wenwu; ZHU Zengrong (浙江大学学报. 农业与生命科学版)
With climate change, global temperatures are expected to rise, posing a pervasive and growing threat to biodiversity and ecosystem stability. As ectotherms, insects are completely dependent on environmental temperature to grow, develop, and regulate various physiological functions. Therefore, global warming is likely to have direct or indirect effects on insect individuals, populations, and their associated communities and food webs. However, many studies have suggested that the species at higher trophic levels seem to be more sensitive to changes in environmental factors, meaning that predators and parasitoids may face more severe challenges than their prey or hosts. In this paper, we analyzed the effects of temperature changes on the development, reproduction, predation and parasitism of insect natural enemies based on existing studies, compared the responses of the same species (different natural enemy species) and different trophic level species (natural enemy and its host or prey) to temperature increase, and summarized the synchronicity changes between natural enemies and pests caused by global warming. Understanding the response of insect predators and parasitoids to temperature rise is of great significance for biological control and ecological governance of agricultural pests in a warming climate.